Development of Antibody-Oligonucleotide Complexes for Targeting Exosomal MicroRNA - Asako Yamayoshi; Shota Oyama; Yusuke Kishimoto; Ryo Konishi; Tsuyoshi Yamamoto; Akio Kobori; Hiroshi Harada; Eishi Ashihara; Hiroshi Sugiyama; Akira Murakami (MDPI AG, 2020)
MicroRNAs in exosomes (exosomal miRNAs) are considered as significant targets for cancer therapy. Anti-miR oligonucleotides are often used for the functional inhibition of miRNAs; however, there are no studies regarding the regulation of exosomal miRNA functions. In this study, we attempted to develop a novel drug delivery system using anti-exosome antibody-anti-miR oligonucleotide complexes (ExomiR-Tracker) to hijack exosomes to carry anti-miR oligonucleotides inside exosome-recipient cells. We found that ExomiR-Tracker bound to the exosomes, and then the complexes were introduced into the recipient cells. We also found that anti-miR oligonucleotides introduced into the recipient cells can exhibit inhibitory effects on exosomal miRNA functions in vitro and in vivo. We believe that our strategy would be a promising one for targeting exosomal miRNAs.